Urban Concentration and Spatial Allocation of Rents from natural resources. A Zipf's Curve Approach - Dentinho, Tomaz Ponce (REGION, 2017)
<span style="line-height: 115%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This paper aims at demonstrating how countries' dependency on natural resources plays a crucial role in urban concentration. The Zipf's Curve Elasticity is estimated for a group of countries and related to a set of indicators of unilateral transferences. Results show that in comparison to others, countries with higher urban concentration explained by higher Zipf's Curve Elasticity have a higher percentage of income coming from natural resources and education expenditures whereas public spending in health and outflow of Foreign Direct Investment seem to have spatial redistribution effects. Summing up, there are signs that the spatial allocation of property rights over natural resources and related rents influences urban concentration.